Intervensi Kebijakan Pemerintah Kota Pontianak dalam Pengembangan Kelompok Tani Aloe Vera - Fira Murdita; Sanggar Tribuana Tungga Dewi; Ruhilda Utami; Mifta Fania Salsabila; Dini Rahma (CV Global Research Publication, 2025)
This study aims to analyze the form, effectiveness, and determinant factors of the Pontianak City Government's policy intervention in restoring and empowering aloe vera farmer groups. Utilizing a descriptive qualitative research design, this study is focused in the North Pontianak District. Data collection was conducted through in-depth interviews with farmer representatives and officials from the Department of Food, Agriculture, and Fisheries (DPPP), along with field observations and documentation studies. The research findings indicate that the Pontianak City Government has implemented four dimensions of structural intervention: production facilities and infrastructure assistance (including the distribution of operational vehicles to overcome upstream logistical constraints), training programs for derivative product diversification and multiculture planting patterns, marketing facilitation through the integration of the Aloe Vera Center ecosystem, and comprehensive capital access assistance. The discussion reveals that this intervention has proven effective in restoring farmers' fundamental motivation and operational mobility in the short term. Nevertheless, long-term effectiveness is still hindered by the slow adaptation to post-harvest technology, market price disparities, and suboptimal institutional synergy between the upstream and downstream industrial sectors. This study concludes that empowering urban farmers requires a paradigm shift from a charitable approach to participatory ecosystem governance.